2005
DOI: 10.1002/adic.200590076
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multivariate Analysis of MIR Spectra to Study Bread Staling

Abstract: Different kinds of bread, stored at constant temperature and at controlled humidity conditions for a week since their manufacturing date, were analysed by Attenuated Total Reflectance‐Fourier Transform InfraRed (ATR‐FTIR) spectroscopy. The collected spectra were processed by Principal Component Analysis (PCA), in order to evaluate the changes occurring during bread ageing. For the sake of comparison, the 1060‐950 cm−1‐1 spectral window has been also investigated by curve‐fitting methods. It was observed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…Cocchi and others () coupled middle‐infrared spectroscopy (MIR) with principal component analysis (PCA) to follow bread shelf‐life in a rapid and affordable way. Spectra of breads stored up to 7 d at ambient temperature were acquired in attenuated total reflection mode with an FTIR spectrometer, normalized and then subjected to PCA.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…Cocchi and others () coupled middle‐infrared spectroscopy (MIR) with principal component analysis (PCA) to follow bread shelf‐life in a rapid and affordable way. Spectra of breads stored up to 7 d at ambient temperature were acquired in attenuated total reflection mode with an FTIR spectrometer, normalized and then subjected to PCA.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…Cocchi et al [21] reported that IR spectroscopy is more rapid, sensitive, and cheaper than other methods used to measure bread staling. They reported that mid infrared spectroscopy (MIR) is easier to interpret than NIR and more valuable in observing the molecular conformational changes, while NIR was better in reflecting chemical and physical aspects of bread staling especially those related to hydrogen bonding during starch crystalline network formation.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that mid infrared spectroscopy (MIR) is easier to interpret than NIR and more valuable in observing the molecular conformational changes, while NIR was better in reflecting chemical and physical aspects of bread staling especially those related to hydrogen bonding during starch crystalline network formation. Cocchi et al [21] used MIR spectroscopy and principle component analysis (PCA) as a rapid and cheap method to monitor the bread staling during a storage period of one week. Ringsted et al [22] reported the use of a 2D MIR-NIR correlation spectroscopy successfully to evaluate wheat bread crumb staling during aging.…”
Section: Introductionmentioning
confidence: 99%
“…Assim, a avaliação da distribuição de picos em diversas regiões do espectro de infravermelho gera a necessidade de utilização de ferramentas quimiométricas que permitam a compressão de dados sem que haja perda de informação relevante 6,11,12 . A associação entre a espectroscopia no infravermelho e procedimentos quimiométricos, como a Análise por Componentes Principais (ACP), tem recebido muita atenção de pesquisadores de diversas áreas 4,7,10,14 , por se tratar de uma ferramenta analítica rápida que pode detectar diferentes tipos de adulterações em uma única análise.…”
Section: Introductionunclassified